The effectiveness of procurement department towards the process of purchasing goods at Petrofac Malaysia / Ahmad Adiputra Selamat - Selamat, Ahmad Adiputra (Faculty of Business and Management, 2009)
This study is conducted as a partial fulfillment of the coursework of Project paper (IBM 662). Title of the study is “The Effectiveness of Procurement Department towards the Process of Purchasing Goods at Petrofac Malaysia”. The main objective of the study is to compare the current process of purchasing goods at Petrofac Malaysia with what was suggested by MDT International in their training manual “Procurement and Supply Chain Management – How to Manage the Successful Contracts” produced in 2007 whether there was gaps identified or not. Besides, the researcher also would like to identify any deficiencies that might occur during the process of purchasing goods at by Procurement Department at Petrofac Malaysia. The study was conducted under two types of data collections; Primary data and Secondary data. The primary data was collected from the series of discussions with inter-department’s staffs at Petrofac Malaysia such as Human Resource, IT, Drilling, Subsurface, Production, Finance and Corporate Affairs. In the other hand, secondary data was collected from various source like internet, Petrofac’s Annual Report, magazines, newspapers, journals, books and articles that related to the topic of the study.